One fancy day - Stephens, Elle; Aikins, Dave; Nickelodeon (Television network) (New York : Random House, 2023)
Can SpongeBob and Patrick handle babysitting Narlene's wild little brother Nobby? And should they be worried when he's too well behaved?
"Based on the teleplay 'My Fair Nobby' by Andrew Goodman."
Keywords: SpongeBob SquarePants -- (Fictitious character) -- Juvenile fiction; SpongeBob SquarePants -- (Fictitious character) -- Fiction; SpongeBob SquarePants -- (Fictitious character).; Camps -- Juvenile fiction; Babysitting -- Juvenile fiction; Marine animals -- Juvenile fiction; Best friends -- Fiction; Babysitting -- Fiction; Camps -- Fiction; Humorous stories; JUVENILE FICTION / Animals / Marine Life; JUVENILE FICTION / Readers / Beginner; Babysitting; Camps; Marine animals; Readers; Children's stories; Fiction; Juvenile works; Readers (Publications).